2016
DOI: 10.4172/2155-9899.1000393
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serum Biomarkers in Early Detection of Non-Alcoholic Steatohepatitis and Fibrosis in West Virginian Children

Abstract: Background Obesity, an epidemic among West Virginia children, as well as insulin resistance (IR), is well-established contributors to nonalcoholic steatohepatitis (NASH). Progression of NASH can lead to hepatic fibrosis and cirrhosis, making early detection imperative. The standard for diagnosing NASH is histologically via liver biopsy, which is highly invasive and generally contraindicated in children. By studying serum biomarkers associated with NASH, we aim to identify high risk children who can benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“… Higher circulating FGF-21 in women, but not in men, with LEAD compared to those without LEAD. Sodhi (2016) 60 Cross-sectional Obese children with IR (27) or without IR (16) vs lean controls without IR (28) Higher circulating FGF-21 in obese children with or without IR compared to lean controls. Waluga (2017) 64 Cross-sectional Women with severe obesity and biopsy-defined NAFLD or non-NAFLD during bariatric surgery (56) Similar circulating FGF-21 and hepatic FGF-21 mRNA in different degree of NAS.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… Higher circulating FGF-21 in women, but not in men, with LEAD compared to those without LEAD. Sodhi (2016) 60 Cross-sectional Obese children with IR (27) or without IR (16) vs lean controls without IR (28) Higher circulating FGF-21 in obese children with or without IR compared to lean controls. Waluga (2017) 64 Cross-sectional Women with severe obesity and biopsy-defined NAFLD or non-NAFLD during bariatric surgery (56) Similar circulating FGF-21 and hepatic FGF-21 mRNA in different degree of NAS.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…However, a limitation of many of these studies was that NAFLD patients had higher body mass index (BMI) and/or waist circumference than controls, which may have distorted the association between FGF-21 and NAFLD, since FGF-21 is also upregulated in obesity. 52 , 54 , 58 , 60 On the other hand, limited data from patients with NAFLD and T2DM or IR showed that FGF-21 may not be largely affected by T2DM 53 or IR 60 specifically in NAFLD patients, which may imply that NAFLD itself is a more important drive than T2DM or IR for FGF-21 upregulation. Other authors also speculated that FGF-21 is more closely associated with lipid metabolism than glucose metabolism and IR.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…According to a Chinese prospective study, this protein is an independent predictor of NAFLD[ 31 ]. The possible use of FGF-21 as an NAFLD marker has also been described in an American study conducted in children[ 32 ]. However, the above study demonstrated significant relationships between the level of this marker and the prevalence of obesity, with or without insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing number of patients developing NASH-related end-stage liver disease, the development and validation of non-invasive biomarkers that accurately diagnose and predict clinically relevant outcomes to monitor both NAFLD and fibrosis are critically needed. The findings from our laboratory previously demonstrated the correlation between obesity, insulin resistance and biomarkers associated with NASH in pediatric patients from WV [55]. Owing to the increasing burden of obesity, metabolic disease and poor health care system, the risk of developing NAFLD in WV population is very high, especially in the female population.…”
Section: Introductionmentioning
confidence: 86%